(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the study of the conceptual role and significance of bar self-government through the prism of ensuring a mechanism for the practical implementation of the rule of law as a pan-European value and an integral part of a developed democratic society. It has been determined that conceptually the goal of bar self-government is not simply to resolve internal organizational and functional issues of the bar, but to create such optimal conditions of organization and activity under which the institute of the bar is able to fully realize its social role and purpose, to function in the most rational way for the effective implementation of the tasks assigned to it, which correspond to the common values certified by Ukraine on which the European Union is built, such as: respect for human dignity, freedom, democracy, equality, the rule of law and observance of human rights. It has been proven that the self-government of the bar is an important element of the institutional component of the mechanism for ensuring and implementing the Ukrainian «formula» of the rule of law, enshrined in the Constitution of Ukraine, according to which the rule of law is not only declared, but also acts in the practical plane, and therefore acts as its inseparable, directly practical implementation component.